Croatian Society of Medical Biochemistry and Laboratory Medicine : national recommendations for blood collection, processing, performance and reporting of results for coagulation screening assays prothrombin time, activated partial thromboplastin time - Bronić, Ana (Array, 2019)
A modern diagnostic laboratory offers wide spectrum of coagulation assays utilized in the diagnosis and management of patients with haemostatic disorders, preoperative screening and anticoagulation therapy monitoring. The recent survey conducted among Croatian medical biochemistry and transfusion laboratories showed the existence of different practice policies in particular phases of laboratory process during coagulation testing and highlighted areas that need improvement. Lack of assay standardization together with non-harmonized test results between different measurementmethods, can potentially lead to incorrect decisions in patient’s treatment. Consequently, patient safety could be compromised. Therefore, recommended procedures related to preanalytical, analytical and postanalytical phases of prothrombin time, activated partial thromboplastin time, thrombin time, fibrinogen and D-dimer testing are provided in this review, aiming to help laboratories to generate accurate and reliable test results.